PENATALAKSANAAN FISIOTERAPI PADA KASUS CHRONIC ANKLE INSTABILITY UNTUK MENINGKATKAN STABILITAS DENGAN MODALITAS TENS DAN STAR EXCURTION BALANCE EXERCISE - Laily Rizqiah; Dian Intan Permatasari; Enny Fauziah (UPPM Politeknik Unggulan Kalimantan, 2025)
Chronic Ankle Instability (CAI) is a condition resulting from previous ankle injuries, which can lead to damage to the ligaments and other structures of the ankle. This condition often results in deterioration and is known as chronic ankle instability. This study aims to improve stability in cases of Chronic Ankle Instability using the modalities of Transcutaneous Electrical Nerve Stimulation (TENS) and Star Excursion Balance Exercise (SEBE). This research employs a descriptive quantitative approach with a case study design to determine the benefits of TENS and SEBE modalities. Based on inclusion and exclusion criteria, 3 respondents were identified. The study results showed that the highest incidence of positive CAI was at the age of 16 years (66.3%), with all participants being male (100%). The application of TENS and SEBE modalities was found to improve stability in cases of Chronic Ankle Instability.